2006
DOI: 10.1111/j.1525-1497.2006.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

A prescription for cultural competence in medical education

Abstract: Cultural competence programs have proliferated in U.S. medical schools in response to increasing national diversity, as well as mandates from accrediting bodies. Although such training programs share common goals of improving physician-patient communication and reducing health disparities, they often differ in their content, emphasis, setting, and duration. Moreover, training in cross-cultural medicine may be absent from students' clinical rotations, when it might be most relevant and memorable. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
150
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(154 citation statements)
references
References 49 publications
(59 reference statements)
1
150
1
2
Order By: Relevance
“…medical schools generally include cultural competency education within required courses 32 . However, few medical schools have achieved longitudinal integration of issues of culture into 4-year curricula 33,34 instead concentrating in the first or second years of medical school, often in a didactic or case-based format 35 .…”
Section: United Statesmentioning
confidence: 99%
“…medical schools generally include cultural competency education within required courses 32 . However, few medical schools have achieved longitudinal integration of issues of culture into 4-year curricula 33,34 instead concentrating in the first or second years of medical school, often in a didactic or case-based format 35 .…”
Section: United Statesmentioning
confidence: 99%
“…The topic of medical education on cultural competency or sensitivity has already been well explored in the literature. [12][13][14] In addition, Spanish is the official language in 21 countries on four different continents, each with vastly different cultures. Thus, addressing cultural competency or sensitivity education was beyond the scope of our survey.…”
Section: Survey Developmentmentioning
confidence: 99%
“…While the manner in which cultural training should best be provided varies in the literature, the need to acknowledge the potential impact of cultural factors is widely supported. 3,9,[11][12][13] A seminal 2005 study by Weissman et al 14 found that the majority of residents (96%) recognized the importance of cultural issues in health care and that 92% of them felt prepared to address general culturally related care issues; however, with regard to specific components of culturally sensitive approaches to care, only 75% responded affirmatively. An overly generic approach (ie, lack of explicit cultural training) may underestimate the diversity of the Objective We reviewed Accreditation Council for Graduate Medical Education (ACGME) program requirements and relevant documents from the ACGME website to evaluate competency requirements across specialties.…”
Section: Introductionmentioning
confidence: 99%